MANAGEMENT COMPETENCE AND ITS SIGNIFICANCE IN DEVELOPING ORGANIZATIONAL ABILITY - Otabek Abduxamidovich, Abdug’aniyev (PT. Antis International Publisher, 2024)
Objective: This study aims to explore the concept of managerial competence, focusing on its significance in leadership and organizational success. The research investigates how competence influences management practices and the development of leadership qualities across different contexts. Methods: The research utilizes a mixed-methods approach, which includes a comprehensive literature review of competence theories, psychometric assessments using the KOS-1 method, and case studies. These methods evaluate the application of social-psychological competencies such as communicative, perceptive, and interactive competence. Surveys and interviews were also conducted with managers to understand the key competencies required in leadership roles. Results: The findings reveal that managerial competence significantly impacts team performance, decision-making, and innovation. Competence is not only determined by education but also by the ability to influence others, manage complex tasks, and adapt to changing circumstances. Managers who demonstrate high levels of competence foster a positive organizational environment, motivating their teams and driving organizational success. Novelty: The novelty of this study lies in the integration of historical leadership perspectives, such as those of Abu Nasr Farabi, with contemporary methods for assessing managerial competence. This approach provides a comprehensive framework for understanding how managers can develop and apply their competencies to enhance both personal and organizational performance.